Giá trị kiến thức truyền thông địa phương đối với ứng phó biến đổi khí hậu vùng ven biển và hải đảo - Chung, Võ Trí (2016)
Vietnam is one of five countries in the world which will be affected most seriously by climate change according to international forecasts, particularly its coastal and island regions. Its long coast and its archipelago of marine islands stand in the front lines of coming natural disasters. How can the negative impacts arising from climate change be prevented or mitigated where there is such high population density and focal economic and industrial zones? Application of modern measures should be harmonized with local traditional knowledge in facilitating adaptation solutions to climate change, especially on the coast. Classification of local communities and identification of traditional knowledge categories, as in current trends in human ecology, could be important and necessary in this case study.